SO2 gas sensing characteristics of FET- and resistor-type gas sensors having WO3 as sensing material. (March 2020) - Jung, Gyuweon; Jeong, Yujeong; Hong, Yoonki; Wu, Meile; Hong, Seongbin; Shin, Wonjun; Park, Jinwoo; Jang, Dongkyu; Lee, Jong-Ho
Highlights: SO2 sensing characteristics of the FET- and resistor-type sensors are investigated. 18-nm-thick WO3 film is used as a sensing layer. Applying a negative pre-bias to the FET-type gas sensor increases the response. Abstract: Sensing characteristics of the SO2 gas are investigated using a horizontal floating-gate FET-type gas sensor. SO2 gas sensing characteristics of the resistor-type gas sensor, a conventional sensor, fabricated on the same wafer are also investigated and compared with the FET-type gas sensor. The 18-nm-thick WO3 deposited using a radio frequency magnetron sputtering method is used as the sensing material. The SO2 gas sensing characteristics are examined while varying the operating temperature, the concentration of the SO2 gas, and the pre-bias ( V pre ). The sensing mechanism for detecting the SO2 gas in an FET-type gas sensor is examined. Both sensors are able to detect up to 10 ppm of SO2 gas, and the FET-type sensor shows significantly improved gas response by using the pre-bias scheme.